Whole-Body Vibration Exercise for Knee Osteoarthritis: A Systematic Review and Meta-Analysis. (5th August 2015) - Li, Xin; Wang, Xue-Qiang; Chen, Bing-Lin; Huang, Ling-Yan; Liu, Yu
Abstract : Objectives . To assess the effects of WBV exercise on patients with KOA. Methods . Eight databases including Pubmed, EMBASE, Cochrane Library, CINAHL, Web of Science, the Physiotherapy Evidence Database, CNKI, and Wanfang were searched up to November 2014. Randomized controlled trials (RCTs) of WBV for KOA were eligible. The outcomes were pain intensity, functional performances, self-reported status, adverse events, and muscle strength. A meta-analysis was conducted. Results . Five trials with 168 participants provided data for the meta-analysis. No significant difference was shown in pain intensity and self-reported status between WBV and other forms of exercise. Improvement in functional performance (evaluated by BBS; WMD, 2.96; 95% CI, 1.29 to 4.62;P = 0.0005 ) was greater in WBV group, but the other parameters of functional performance (including 6MWT and TGUG) revealed no statistically significant difference. Adverse events were only reported in one trial and no significant difference was discovered in muscle strength. The overall quality of evidence was very low. Conclusion. Currently there is only limited evidence that suggested that WBV is effective in the treatment of KOA. Large, well-designed RCTs with better designs are needed.